Association of internal training load with changes in aerobic endrance and strength/power variables in professional soccer players during the pre-season - Papadakis, L.; Tymvios, C.; Patras, K. (Biology of Exercise, 2019)
To examine the association between training load and aerobic fitness and strength/power, sixteen soccer players were tested pre and post pre-season for velocity at 2mM and 4mM, peak treadmill velocity, squat jump and countermovement jump. Practical significance of the changes was assessed with magnitude-based inferences. Pearson`s correlation coefficients were calculated to establish the associations between training load and the tested variables. There was an almost certainly moderate increase for velocity at 2mM [ES= 0.86 (0.54; 1.18)], an almost certainly very large increase for velocity at 4mM [ES= 1.32 (0.94; 1.69)], an almost certainly large increase for peak treadmill velocity [ES= 1.11 (0.63; 1.58)], and a likely moderate increase for squat jump [ES= 0.37 (0.06; 0.69)] and countermovement jump [ES=0.45 (0.19; 0.72)]. Training load had a most likely large positive correlation to velocity at 4mM [r=0.74(0.46;0.89)], a likely moderate positive correlation to velocity at 2mM [r=0.39(-0.04;0.70] and a likely moderate negative correlation to squat jump (r=-0.33(-0.66;0.11). Training load has a strong positive correlation to improvements in aerobic endurance and weak negative correlation on improvements in strength/power. Prioritizing training goals and adjusting the dose of the training load will gauge endurance adaptations with as minimal as possible negative impact on strength/ power adaptations.